Xanthogranulomatous Pyelonephritis Incidentally Detected in a Young Infant - Jeena Annie Philip; R. Veena; Christy Cathreen Thomas; Radhika C. Radhakrishnan; Ashok Kumar; Susan Uthup (Indian Pediatrics Case Reports)
Background: Xanthogranulomatous pyelonephritis (XGP) is a chronic inflammatory condition of the kidney, rarely reported in children, and often misdiagnosed as a neoplasm. Clinical Description: A 2-month-old preterm baby boy was hospitalized for bronchiolitis. Examination showed tachypnea, normal pulses, improper weight gain since birth, hypertension and was incidentally detected to have palpable right kidney, without any abnormality in urinary stream. Management and Outcome: Routine blood investigations and urinalysis were normal. Chest X-ray was consistent with bronchiolitis and the baby was managed accordingly along with nifedipine for hypertension. Ultrasound abdomen showed an enlarged right kidney with hypoechoic mass in the upper pole and magnetic resonance imaging further showed the mass having areas of necrosis infiltrating into surrounding tissues. Considering a possibility of neoplasm, nephrectomy was performed. However, histopathological evaluation showed evidence of XGP. The baby thrived well, postnephrectomy and remained asymptomatic. Conclusion: This case creates awareness regarding occurrence of XGP in such a young infant, where diagnosis was made incidentally, only during a thorough systemic examination, followed by radiological imaging and histopathology.